Happiness is a warm gun? Gun ownership and happiness in the United States (1973-2018) - Terrence D. Hill; Benjamin Dowd-Arrow; Andrew P. Davis; Amy M. Burdette (Elsevier, 2020)
Although there is no empirical evidence linking gun ownership with happiness, speculation is widespread. In this paper, we assess the association between gun ownership and happiness. We use 27 years of national cross-sectional data from the General Social Survey (1973-2018) and logistic regression to model self-rated happiness as a function of gun ownership (n = 37,960). In bivariate and partially adjusted models, we observed that the odds of being very happy were higher for respondents who reported having a gun in their home. This association persisted with adjustments for age, gender, race/ethnicity, education, employment status, household income, financial satisfaction, financial change, number of children, religious attendance, political affiliation, urban residence, region of interview, and survey year. In our fully adjusted model, gun ownership was unrelated to happiness. The original association between gun ownership and happiness was entirely confounded by marital status. In other words, gun owners only appeared happier because they are more likely to be married, which increases happiness. In the first study of gun ownership and happiness, we found that people who own guns and people who do not own guns tend to exhibit similar levels of happiness. This general pattern was consistent across nearly three decades of national surveys, a wide range of subgroups, and different measures of happiness. Our analyses are important because they contribute to our understanding of the epidemiology of happiness. They also indirectly challenge theoretical perspectives and cultural narratives about how guns contribute to feelings of safety, power, and pleasure.